Respuesta :

Answer:

the last option: [tex]f(-2)=g(-2)[/tex]

Step-by-step explanation:

Make sure you have the numerical answer for each of the functional expressions that are shown among the possible solution choices:

f(4) = -14  (what the blue function reads  [its y-value] when x is 4)

g(4) = 10  (what the red function reads [its y-value] for x=4)

g(-2) = 4 (y-value of the red function when x is -2)

f(2) = -8 (y-value of the blue function for x = 2)

f(-2) = 4 (y-value of the blue function for x =-2)

use them to compare the options they give you, and the only one that matches is the last option.

ACCESS MORE